THE INFLUENCE OF FINANCIAL LITERACY ON THE SAVING BEHAVIOR OF GENERATION Z AT POLITEKNIK LP3I JAKARTA CENTRAL JAKARTA CAMPUS - Ferdy Andika; Muhammad Ilyas Abdilah; Bintang Fajar Maulana (IC-BESTS: International Conference on Business, Economics, Technology, and Social Sciences, 2026)
This study examines the effect of financial literacy on the saving behavior of Generation Z students at Politeknik LP3I Jakarta, Central Jakarta Campus. Generation Z is often characterized by consumptive tendencies and low financial literacy, which is reflected in inconsistent saving habits. A quantitative descriptive method was used, with data collected through a questionnaire distributed to student respondents from several study programs at the campus, selected through non-probability sampling. Data were analyzed using multiple linear regression with the assistance of IBM SPSS. Validity and reliability tests confirmed that all questionnaire items were valid and reliable, indicating that the instrument was appropriate for measuring financial literacy and saving behavior. Classical assumption tests showed that the data were normally distributed and free from multicollinearity and heteroscedasticity, confirming that the regression model was suitable for analysis. The regression analysis revealed that financial literacy has a positive and statistically significant effect on saving behavior, with a substantial contribution to explaining variation among Generation Z students. These findings support the Theory of Planned Behavior, in which financial understanding acts as a form of perceived behavioral control that fosters saving habits, and confirm that stronger financial literacy corresponds to better and more consistent saving behavior among Generation Z.